P13.12 Hiv sensitisation health care worker training in vanuatu. (13th September 2015) - Coote, K; Kishore, K; Bates, N; Prasad, P
Abstract : Introduction: College of Medicine, Nursing and Health Sciences (CMNHS) in collaboration with The Albion Centre (Albion) conducted a 2-day HIV Sensitisation workshop in Port Vila, Vanuatu from 10 th – 11 th March 2015. The HIV Sensitisation training is an activity of the Pacific Health Worker Support Project. The HIV Sensitisation training aims to positively reshape health workers' perceptions about HIV and people from key populations (KP), including sex workers, men who have sex with men and PLHIV, by: Addressing shortfalls in knowledge and understanding about HIV; Demystifying/clarify personally-held attitudes and beliefs about HIV and PLHIV; and Learning about the perspectives and experiences of KP. Methods: This training was provided by two representatives from KP groups, who had previously completed training-of-trainers (ToT) workshops in Suva, Fiji. Results: Altogether 24 health workers, including representation from all six Vanuatu provinces attended the two-day workshop. The workshop was evaluated using two mechanisms: a Knowledge, Attitudes and Practices Survey (KAPS) administered to participants at pre and post training; and an anonymous course evaluation form, administered to participants at post training. Participants demonstrated improvement in all areas; however a paired-samples t-test analysis indicated that this improvement was significant only in the area of improved knowledge, across the group. Some of the key themes which emerged from the evaluations included that the training: raised their awareness of KP and challenged their personal attitudes; heightened their awareness of how stigmatising language and behaviour can alienate KP; and was needed through-out the healthcare workforce in Vanuatu. Conclusion: Overall the HIV Sensitisation Training workshop in Vanuatu was a success. The 2-day training raised their awareness of KP and challenged their personal attitudes; heightened their awareness of how stigmatising language and behaviour can alienate KP; and was needed through-out the healthcare workforce in Vanuatu. Disclosure of interest statement: The Pacific Sexual Health and HIV Health Worker Support Project is funded by Australian aid's Regional HIV/AIDS Capacity Building Program (2012–2015). No pharmaceutical grants were received in the development of this study.